OPTIMALISASI EDUKASI DIGITAL DAN PARTISIPASI MASYARAKAT DALAM MITIGASI BENCANA MELALUI SOSIALISASI APLIKASI LENCANA BMKG - Tri Suwito Abdhy; Dian Herdianingsih; Tri Nurmayati; Famiyana Dewi; Citra Kusmardani; Dwi Rachmadi; Hanapi; Dwi Yuwono; Tukiyat (Abdi Jurnal Publikasi, 2025)
This Community Service Program (PKM), organized by Master of Informatics Engineering (S-2) students of Pamulang University (UNPAM), focuses on the Optimization of Digital Education and Public Participation in Disaster Mitigation. The core objective of this activity was to enhance the preparedness and capacity of staff and employees at the Bekasi City Transportation Agency Office through intensive socialization of the BMKG 'Lencana' Application. The threat of natural and non-natural disasters requires a rapid and accurate digital response. The Lencana BMKG Application offers a near-real-time solution for reporting and accessing weather and disaster information. The methods employed included comprehensive outreach, demonstration of application features such as Weather Report, Earthquake Report, and Flood Report, alongside interactive practice to train participants as 'Citizen Reporters' ('Reporter Netizen'). The results indicated a significant increase in digital disaster mitigation literacy among participants, who now possess a better understanding of using the application as both an information source and a means of contributing data. This successful PKM reflects UNPAM's commitment to the Tridharma of Higher Education in building a more resilient community through information technology utilization. The main outcome is the creation of digital-based disaster mitigation agents within the Bekasi City Transportation Agency environment.